Correlation of Anterior Interbody Graft Choice With Patient-Reported Outcomes in Cervical Spine Trauma. Issue 7 (October 2019) - Lee, Hui Qing; Kow, Chien Yew; Ng, Jay Shen; Chan, Patrick; Ton, Lu; Etherington, Greg; Liew, Susan; Hunn, Martin; Fitzgerald, Mark; Tee, Jin
Study Design: Ambispective observational cohort study. Objectives: Synthetic graft usage avoids morbidity associated with harvest and reduces operative time. This study aims to evaluate outcomes of anterior cervical stabilization surgery using a synthetic cage in comparison with iliac crest bone graft (ICBG) following cervical spine trauma. Methods: An ambispective review was conducted on patients from the Alfred Trauma Registry. Consecutive patients treated at a level 1 trauma center, aged 18 years and older who were treated with standalone anterior cervical stabilization following spine trauma (2011-2016) were included in the study. Primary outcome measures were patient overall satisfaction, Neck Disability Index (NDI), neck pain 10-point visual analogue scale (VAS-neck) and arm pain 10-point visual analogue scale (VAS-arm). Secondary outcome measures were radiographic evidence of fusion and rate of revision surgery. All patients had follow-up for at least 1 year. Results: Between 2011 and 2016, 114 traumatic disc levels in 104 patients were treated. ICBG was used in 32% and polyetheretherketone (PEEK) cage in 68% of the patients. Both groups had similar demographic metrics. There was no significant difference in primary outcome measures between the graft types: (1) patient satisfaction ( P = .15), (2) NDI ( P = .11), (3) VAS-neck ( P = .13), and (4) VAS-arm ( P = .20). Radiology based fusion assessment 6 months postsurgery did not show statistical significance ( P = .10). The rates of revision surgery were similar. Conclusions: This study showed no significant difference in patient-reported outcome measures when comparing the usage of PEEK cage and ICBG in anterior stand alone cervical spine stabilization. Level 1 evidence studies are required to further investigate this finding.